Hollow carbon spheres decorated by silver nanocubes as the advanced aptasensing interface for sensitive and selective tracing of methamphetamine in human biofluids - Zeynab Khorablou; Faezeh Shahdost-Fard; Habib Razmi (Biosensors and Bioelectronics: X, 2023)
This study presents a sensitive and selective aptasensor for the detection of trace amounts of MAMP. The aptasensing principle relies on modifying the planar screen-printed carbon electrode (SPCE) with the synthesized nanostructures of N-doped hollow carbon spheres (N-HCSs) and silver nanocubes (AgNCs). The nanocomposite has presented high active surface area and more electron transfer ability than bare SPCE surface. Furthermore, AgNCs in the nanocomposite acts as a linker to load high amounts of aptamer (Apt) biocaptures on the modified SPCE surface. By MAMP incubation on the embedded interface sensing, Apt arm wrapped around MAMP and the more space barrier induced on the surface and reduced the electrochemical signal of ferro/ferri cyanide as the anion redox probe. The aptasensor affinity toward MAMP led to a wide linear dynamic range (LDR) value from 1.00 pM to 50.00 mM with a low limit of detection (LOD) value of 3.33 × 10−4 pM compared to other electrochemical sensors with no significant interference from other common species. The aptasensor efficiency for MAMP measurement was satisfactory evaluated in some spiked and non-spiked serum, urine and saliva samples from a healthy and addicted person for MAMP. These acceptable results may promise the reliability of the proposed methodology for routine MAMP tests, especially saliva monitoring as the non-invasive analysis. The sensitivity and selectivity of the aptasensor, which is a bonus to accurate and valid discrimination of MAMP, holds great promise to provide technical support for routine analysis of real-world clinical samples.